The nutritional and feeding status of children living in selected residential child care facilities in Zambia: implications for programs and policies - Makhoul, Zeina; Ndonji, Mulemba; Long, Julie M.; Moore, Carolyn; Lunda, Edgar; Mwandileya, Watson; Taren, Douglas (Frontiers in Public Health, 2024)
Introduction This study aimed to estimate the prevalence of undernutrition and risk of feeding difficulties and describe common feeding practices for children from birth to 10 years of age living in residential care in Zambia. Methods This was a secondary analysis of de-identified cross-sectional data on 397 children living in 22 residential care facilities in four provinces. Child demographics, anthropometrics, hemoglobin levels, risk for feeding difficulties, and facility-level feeding practices were collected by a trained study team using Count Me In, a digital health app. Interviews with staff were conducted at 15 residential care facilities. Results Around half of the study sample were boys (53.4%) and <5 years old (55.4%). Special healthcare needs were reported in 10.3% of the children, with cerebral palsy being the most common (3.5%). Underweight, stunting, wasting (using weight-for-length/height), and anemia were found in 22.4, 28.0, 7.1 and 54.7% of children, respectively, with higher rates in children with special healthcare needs and children <24 months old. Duration of residential care was positively associated with length/height-for-age but not weight-for-age or weight-for-length/height z-scores. A risk for feeding difficulties was found in 41.4 and 26.0% of children with and without special healthcare needs, respectively. Suboptimal bottle-feeding practices, including the use of altered nipples and poor caregiver-infant interactions, were observed for infants <12 months old. Residential care staff reported suboptimal diets in their facilities and gaps in knowledge and resources to meet children’s nutritional needs. Conclusion These results demonstrate that a large proportion of children living in residential care in Zambia are at high risk for undernutrition and feeding difficulties and contribute to the small body of literature on children living in residential care, both in Zambia and globally. In the context of Zambia’s efforts to improve child nutrition and reform its alternative care, these findings can inform programming and policies for children living in residential care to fulfill their rights to health and family care.